An integrated multi-omics study of key mediators and therapeutic targets for doxorubicin-induced atrial fibrillation - Zhenli Li; Sihan Liu; Jing He; Tenghui Wang; Jingtao Ma (PLoS ONE, 2026)
Background Doxorubicin (DOX), a widely used chemotherapeutic agent for cancer patients, is associated with a significant risk of inducing atrial fibrillation (AF), a serious cardiac complication that impairs patient prognosis. However, the specific molecular and cellular mechanisms linking DOX cardiotoxicity to AF pathogenesis remain poorly understood. Methods Following processing pharmacovigilance analysis of DOX-related AF events, we employed an integrative multi-omics strategy. Differentially expressed genes (DEGs) were first identified from the atrial transcriptomic dataset. Network toxicology was used to predict DOX targets, which were intersected with AF-related genes and DEGs to identify candidate targets. Functional analyses and protein-protein interaction network analysis was applied to pinpoint hub genes. Their predictive performance was validated in independent datasets. Gene set enrichment analysis (GSEA) and immune infiltration profiling (CIBERSORT) were conducted to elucidate biological functions and immune context. Molecular docking simulations validated direct interactions between DOX and selected proteins. Finally, single-cell RNA sequencing (scRNA-seq) analysis resolved the cell-type-specific expression patterns of key targets. Results Functional analyses implicated the candidate genes in critical pathways. 5 hub genes were further selected from candidate genes using the MCC algorithm. Among 5 hub genes, we identified and validated the combination of CCR2 , PDE5A , and CXCR2 showed high predictive accuracy for AF (mean AUC = 0.87), with identifying and validating CCR2 and PDE5A significantly and differentially expressed. GSEA linked CCR2 and PDE5A showed different pathways. Immune infiltration analysis revealed significant alterations in macrophages, monocytes, and T cell subsets in AF tissues. Molecular docking confirmed stable, high-affinity binding between DOX and both CCR2 and PDE5A (binding energy < −7 kcal/mol). Crucially, scRNA-seq analysis demonstrated that CCR2 and PDE5A were differentially expressed in atrial macrophages and fibroblasts respectively. Conclusion This study suggests that CCR2 and PDE5A may serve as central mediators and potential therapeutic targets for DOX-induced AF, though these findings require experimental validation.